PENGARUH PELATIHAN, LINGKUNGAN KERJA DAN PENEMPATAN KERJA TERHADAP PRESTASI KERJA PADA SUPER MARKET PAMELA CABANG KUSUMANEGARA YOGYAKARTA - adit nurhadi karlos (JURNAL EKOBIS DEWANTARA, 2018)
This study aims to analyze the effect of training on job performance, the influence of work environment on job performance, the influence of job placement on job performance, and the effect of training, work environment and work placement together on the performance of Super market Pamela kusumanegara branch in Yogyakarta The population in this research is all employees of 38 people in Super market Pamela kusumanegara branch in Yogyakarta using technique saturated samples of research, variables studied by the authors include Training (X1), Working Environment (X2), Work Placement (X3) and Job Performance (Y). Data collection method used questionnaire method, while data analysis technique used multiple regression analysis supported by F test and T test and classical assumption test consist of multicolinearity test, normality test, and heterokedastisity test. The result of research with significance level of 5% or 0,05 indicates that training has significant effect on work performance (0,020 <0,05), work environment has significant effect on work performance (0,021 <0,05), and work placement have significant influence to work performance (0.008> 0.05). Simultaneously the variables of training, work environment, and job performance have a signif